The Interaction of Information and Measurement Perspective in Decision Usefulness Approach of Accounting Information - PINASTI, MARGANI (The Indonesian Journal of Accounting Research, 2012)
This research examines the moderating effect of scope of disclosure on the correlation between earnings quality and earnings value relevance, and testing the moderating effect of earnings quality on the correlation between scope of disclosure and disclosure information content. This testing was done in order to analyze interaction between an information perspective and a measurement perspective. The interaction of these two perspectives is important, because two aspects of them, namely accounting number quality and largely disclosing information, cannot be ignored. Information perspective needs to consider the accounting number quality, and measurement perspectives needs to consider the size of disclosure. In this research, propositions about interaction of these two perspectives were developed and tested empirically. The results support measurement perspective and information perspective, and also support the proposition of interaction of these two perspectives. Result of empirical testing show a moderating effect of scope of disclosure on the correlation between earnings quality and earnings value relevance. The larger the disclosure, the weaker the correlation between earnings quality and earnings value relevance. This effect shows a role of scope of disclosure in measurement perspective as a source of alternative information for financial report users. The findings also indicate the presence of a moderating effect of earnings quality on the correlation between the scope of disclosure and disclosure information content. The higher the earnings quality, the weaker the correlation between the scope of disclosure and information content. This effect shows the role of earnings quality in information perspective; good quality of earnings can absorb information, so that it will decrease information overload in excessive disclosure.